STUDY OF COMBINING ABILITY ANALYSIS AND GENE ACTION FOR SEED COTTON YIELD AND FIBRE CHARACTERS IN UPLAND COTTON (Gossypium hirsutum L.) - K. BAYYAPU REDDY, V. CHENGA REDDY, M. LAL AHMED and K.V. SIVA REDDY (The Journal of Research ANGRAU, 2017)
Combining ability was studied with ten parents in a diallel crossing design excluding reciprocals along with their parents for seventeen characters in order to identify suitable parents/crosses, which could be utilized in upland cotton (Gossypium hirsutum L.) for further improvement programme. The analysis of variance for combining ability revealed that, the SCA variances were higher than GCA variances for all the characters except for days to 50 % flowering indicating the predominance of non-additive gene action. The estimates of gca effects revealed that the parents NDLH 1938, L 788 and MCU 5 were found to be best general combiners for yield and fibre quality traits in desired direction. The crosses, NDLH 1938 × L 770, L 604 × RAH 1004 and L 788 × G COT 16 recorded high per se performance (111.98, 105.13 and 122.6 g) and significant positive sca effects (51.49, 24.71 and 21.35) for seed cotton yield plant-1 respectively. These hybrids were also recorded high per se performance and significant positive sca effects for number of bolls plant-1, boll weight and lint yield plant-1.